The analysis of genetic aberrations in South African oesophageal squamous cell carcinoma patients - Patten, Victoria Alexandra (Department of Integrative Biomedical Sciences (IBMS), 2023)
Estimates for 2017 indicate that 20% of cancers globally are gastrointestinal tract (GIT) cancers, with oesophageal cancer being the 8th most common cancer. Oesophageal squamous cell carcinoma (OSCC) occurs in the upper to mid oesophagus and is present at high incidence in developing countries including South Africa. There are no early symptoms, resulting in late diagnosis and poor prognosis. In this study, tumour and blood DNA was obtained from 35 OSCC patients and subjected to whole genome sequencing (WGS). Bioinformatics analysis pipelines were designed to identify the possibility of novel viral insertions, investigating Human Endogenous Retroviruses (HERV's) insertions alongside the presence of somatic mutations in patient samples. The aims being to identify integration of any foreign DNA, to investigate if there is any linkage between HERV insertion and somatic mutations, and to identify any somatic mutations of potential interest in the OSCC cohort. The novel virus investigations however, proved to be inconclusive and there appeared to be no link between HERV insertions and somatic mutations present in the patients. Very significantly, it was determined that numerous somatic mutations were present in the MUC3A gene of the patient cohort, an interesting observation as no such previous association with OSCC has been recorded. MUC3A is a membrane-bound glycoprotein component of mucous gels, and its aberrant expression has been correlated with invasion and metastasis in a variety of other cancers. However, due to the complexity of the particular gene sequence and the known inconsistencies of variant calling performed on complex data sets, these mutations should be viewed with extreme caution as they are likely to be false positives. Analysis of RNA-seq data showed a 4.6 log2 fold increase in MUC3A expression in the tumour samples of these OSCC patients, with a P-adjusted value of 7.05e-06, suggesting highly significant differential gene expression. Functional enrichment analysis further showed that MUC3A was significantly associated with one of the top 5 gene ontologies (extracellular matrix structural constituent) for molecular function ontology class together with a number of collagen (COL) and MMP genes known to play a role in oncogenic progression and membrane stiffness. GSEA and KEGG analysis indicated predominantly chemokine/cytokine pro-inflammatory enriched pathways. Immunohistochemistry staining showed 10 out of 13 of the samples had no detectable levels of MUC3A protein, suggesting that the production of a non-functional truncated protein may lead to the upregulation of MUC3A expression that could possibly play a role in downstream pro-oncogenic signalling.